Resenhas - Ana Cecília Acioli Lima; Arryanne Queiroz; Bernadete Grossi dos Santos; Carlos Alexandre Baumgarten; Denise Aparecida Soares de Moura; Katiuscia Maria Lazzarin; Marie Jane Soares Carvalho; Nubia Jacques Hanciau; Nucia Alexandra Silva de Oliveira (Revista Estudos Feministas, 2002)
http://dx.doi.org/10.1590/S0104-026X2002000100018